Analisis Peran Pemberian Sanksi Terhadap Pengembangan Karakter Kesopanan Siswa Kelas IV SD Negeri Wates 2 - Nabila, Nadya Marell; Situmeang, Widia Aprilia; Susanti, Putri Anisa; Listia, Dian; Kiptiyah, Siti Maryatul (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Education is an important part of human life that lasts throughout life, with character education being an important focus in the learning process. This study explores the role of teachers and schools in forming polite character in fourth grade students at SD Negeri Wates 2. Using a qualitative descriptive approach, data was obtained through questionnaires, interviews and documentation. The results of the analysis show that teachers act as role models, instilling the value of politeness, providing guidance, and providing firm consequences. The school supports teachers' efforts through parent education, character development programs, and close collaboration. With cooperation between teachers, schools and parents, it is hoped that students can grow into individuals with quality character.